(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Robust m-Periodogram is used for the analysis of signals with heavy-tailed distribution noise. It is also used for the non-stationary signals in the form of Robust Spectrogram. Robust spectrogram is also used to estimate the instantaneous frequency (IF) of the signal. In this paper, we are introducing a Robust Spectrogram estimator based on Welch Periodogram for estimating the instantaneous frequency of the signal with a time varying window length.